Effects of Pandemic Outbreak on Economies: Evidence From Business History Context - Shang, Yunfeng; Li, Haiwei; Zhang, Ren (Frontiers in Public Health, 2021)
The coronavirus pandemic has highlighted the capitalist dysfunction showing that considering profit over people can be deadly. The study reveals the LME economies were more responsive towards the impact of the disease outbreaks as compared to the CME economies wherein the impact of the disease was moderated by the government involvement. This allows us to draw that the impact of the disease outbreaks can be moderated by increasing the involvement of the government authorities.